The Prediction Of The Influence Of The National Orientation Of Teachers’ Personality On The National Identity Of Pupils. The Case Of Lithuania - Skarbalius, Egidijus; Dirgeliene, Indre (European Scientific Journal, ESJ, 2016)
Given the relevance of a problem emphasized both in the works of scientific research and legal framework the readiness of primary school teachers to educate national identity are going to be analyzed in this article considering the national orientation of teachers’ personality in educating the national identity of pupils. In spring 2014 the research was accomplished by applying quantitative research strategy. The aim of this research was to evaluate how the national orientation of teacher’s personality influences the national identity of pupils. The empirical research has revealed the extraordinary significance of teacher’s personality on the education of national identity in pupils proving at the same time that the younger a child is the stronger influence of teacher’s personality.